Precision medicine at Memorial Sloan Kettering Cancer Center: clinical next-generation sequencing enabling next-generation targeted therapy trials. Issue 12 (December 2015) - Hyman, David M.; Solit, David B.; Arcila, Maria E.; Cheng, Donavan T.; Sabbatini, Paul; Baselga, Jose; Berger, Michael F.; Ladanyi, Marc
Highlights: Comprehensive precision medicine strategies require a comprehensive multidisciplinary approach. Screening assays must be sufficiently broad to identify the full landscape of actionable genomic alterations. Profiling must be applied broadly, irrespective of whether molecular testing is required to guide standard-of-care therapy. Multi-histology biomarker-selected 'basket' studies support treatment based on identified actionable alterations. Abstract : Implementing a center-wide precision medicine strategy at a major cancer center is a true multidisciplinary effort and requires comprehensive alignment of a broad screening strategy with a clinical research enterprise that can use these data to accelerate development of new treatments. Here, we describe the genomic screening approach at Memorial Sloan Kettering Cancer Center, a hybridization capture-based next-generation sequencing clinical assay for solid tumor molecular oncology designated MSK-IMPACT, and how it enables and supports a large clinical trial portfolio enriched for multi-histology, biomarker-selected, 'basket' studies of targeted therapies.